Condemned to be Creative - Varghese Panthalookaran; PANTHALOOKARAN (Varghese) (Kerala Pallikkutam Publications, 2019)
Ability to think in a creative manner is essential for definitive success in life and career. Some are born with those skills; but anybody can nurture them by regular practice. Here is a book that helps cultivate attitudes, values and skills required for creative thinking. It also provides a multitude of techniques to master it. A must read for teachers, students, institution leaders and everyone who would like to develop their creative thinking skills!
Keywords: Creative Mind; Creativity Techniques